An Introduction to Medical Teaching - Jeffries, William B.; Huggett, Kathryn N.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Few faculty members in academic medical centres are formally prepared for their roles as teachers. This work is an introductory text designed to provide medical teachers with the core concepts of effective teaching practice and information about innovations for curriculum design, delivery, and assessment. It offers brief, focused chapters with content that is easily assimilated by the reader. Topics are relevant to basic science and clinical teachers, and the work does not presume readers possess prerequisite knowledge of education theory or instructional design. The authors emphasize application of concepts to teaching practice. Topics include: Helping Students Learn; Teaching Large Groups; Teaching in Small Groups; Problem Based Learning; Team-Based Learning, Teaching Clinical Skills; Teaching with Simulation; Teaching with Practicals and Labs; Teaching with Technological Tools; Designing a Course; Assessing Student Performance; Documenting the Trajectory of your Teaching and Teaching as Scholarship. Chapters were written by leaders in medical education and research who draw upon extensive professional experience and the literature on best practices in education. Although designed for teachers, the work reflects a learner-centred perspective and emphasizes outcomes for student learning. The book is accessible and visually interesting, and the work contains information that is current, but not time-sensitive. The work includes recommendations for additional reading and an appendix with resources for medical education.
Facilitating Student Learning -- Teaching Large Groups -- Teaching in Small Groups -- Problem-Based Learning -- Team-Based Learning -- Teaching Clinical Skills -- Teaching with Simulation -- Teaching with Practicals and Labs -- Teaching with Technological Tools -- Designing a Course -- Assessing Student Performance -- Documenting the Trajectory of Your Teaching -- Teaching as Scholarship.
Keywords: Education; Medical Education; Science -- Study and teaching; Educational tests and measurements; Education; Medical Education; Learning & Instruction; Assessment, Testing and Evaluation; Science Education; Educational Technology